Seawater intrusion mapping using electrical resistivity imaging (ERI) at Malaysian coastal area - Hazreek, Z. A. M.; Hashim, M. M. M.; Asmawisham, A. M. N.; Hafiz, Z. M.; Fairus, Y. M.; Fahmy, K. A.; Ashraf, M. I. M.; Rosli, S.; Nordiana, M. M. (IAEME Publication, 2018)
Natural process of seawater intrusion occurs in many coastal areas all around the world. Previous experiences have recorded that the phenomena will cause a problem to the freshwater aquifer due to its salinity contamination. Conventional approach on saltwater detection also suffers from efficiency in term of cost, time and data coverage. Hence, this study has introduced an electrical resistivity imaging (ERI) for saltwater intrusion mapping based on time lapse condition. Data acquisition and processing of ERI was performed using ABEM SAS 4000 and RES2DINV software. It was found that resistivity value was varied during different water tide due to migration of saltwater and freshwater within the aquifer. Saltwater, brackish water and freshwater was detected based on resistivity values of 0.1 – 5 Ωm, 5 – 15 Ωm and 50 – 100 Ωm respectively. This study was successfully demonstrated the applicable of ERI in saltwater intrusion mapping thus able to contribute to the sustainable future decision planning and development at the study area.